A STUDY OF THE SELECTING CHARGING STATION BETWEEN PANTOGRAPH AND PLUGIN FOR ELECTRIC BUS : A CASE STUDY OF NAKHON RATCHASIMA PROVINCE, THAILAND - Nitikorn Junhuathon, Terapong Boonraksa (International Journal of Advanced Science and Technology, 2020)
This article proposes a study of the selecting charging station between pantograph and plug in for the electric bus in Nakhon Ratchasima province, Thailand, to simulate and compare to find the the suitable scenario to install charging station. The comparisons of charging stations were simulated in 4 cases included (1) using pantograph charging with charging power level of 150 kW (dwell 10 minute, 2 station) (2) using pantograph charging with charging power level of 600 kW (dwell 10 minute, 1 station)(3) using plug in charging with charging power level of 30 kW (dwell 5 minute, 16 station) (4) using plug in charging with charging power level of 150 kW(dwell 10 minute, 2 station) All of the simulations cases were simulated in MATLAB/Simulink software. The simulation results show the comparison results and the most suitable charging station for Nakhon Ratchasima province, Thailand.